Stabilization and Savings Funds for Nonrenewable Resources - Ossowski, Rolando (Occasional Papers; Occasional Paper ;, 2001)
This chapter examines whether funds can help countries pursue good macroeconomic, and especially fiscal policies, and consequent design issues. Nonrenewable resource funds (NRF) have been suggested as a way of dealing with the effects of price variability, making it easier to put revenues aside when prices are high so that they can be made available to maintain expenditures when prices are low. Funds may also serve as mechanisms to allow part of the nonrenewable resource wealth to be shared by future generations. A detailed evaluation of country experience suggests that NRFs have been associated with a variety of operating rules and fiscal policy experience. In several cases, rules have been bypassed or changed and they do not themselves seem to have effectively constrained spending, and the integration of the fund's operations with overall fiscal policy has often proven problematic. Whether the political economy arguments for an NRF outweigh the potential disadvantages will need to be considered based on the situation in each country.